CDC's 6|18 Initiative: A Cross-Sector Approach to Translating Evidence Into Practice. Issue 5 (September 2018) - Seeff, Laura C.; McGinnis, Tricia; Heishman, Hilary
Abstract : Context: As the US health care system continues to undergo dynamic change, the increased alignment between health care quality and payment has provided new opportunities for public health and health care sectors to work together. Program: The Centers for Disease Control and Prevention's 6|18 Initiative accelerates cross-sector collaboration between public health and health care purchasers, payers, and providers and highlights 6 high-burden conditions and 18 associated interventions with evidence of cost reduction/neutrality and improved health outcomes. This evidence can inform payment, utilization, and quality of prevention and control interventions. Implementation: The Centers for Disease Control and Prevention focused initially on public payer health insurance interventions for asthma control, unintended pregnancy prevention, and tobacco cessation. Nine state Medicaid and public health agency teams—in Colorado, Georgia, Louisiana, Massachusetts, Michigan, Minnesota, New York, Rhode Island, and South Carolina—participated in the initiative because they had previously prioritized the health condition(s) and specific intervention(s) and had secured state-level leadership support for state agency collaboration. The Centers for Disease Control and Prevention, the Centers for Medicare & Medicaid Services, the Center for Health Care Strategies, the Robert Wood Johnson Foundation, and other partners supported state implementation and dissemination of early lessons learned. Evaluation: The Centers for Disease Control and Prevention conducted exploratory interviews to guide improvement of the 6|18 Initiative and to understand facilitators, barriers, and complementary roles played by each sector. Monthly technical assistance calls conducted with state teams documented collaborative activities between state Medicaid agencies and health departments and state processes to increase coverage and utilization. Discussion: The 6|18 Initiative is strengthening partnerships between state health departments and Medicaid agencies and contributing to state progress in helping improve Medicaid coverage and utilization of effective prevention and control interventions. This initiative highlights early successes for others interested in strengthening collaboration between state agencies and between public and private sectors to improve payment, utilization, and quality of evidence-based interventions. Abstract : Supplemental Digital Content is Available in the Text.